Rasionalitas Implementasi Chat GPT dalam Pembelajaran Keterampilan Menulis Karya Ilmiah - Veddayana, Campin; Romadhon, Sahrul; Aldresti, Fitri; Suyono, Suyono (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Since its release into the public domain, Chat GPT has taken the world by storm with its advanced capabilities. Chat GPT’s extraordinary ability to produce scientific writing seems to be starting to revolutionize the existing practice of scientific writing. This research is an exploratory study that synthesizes the latest literature to review the opportunities and potential of Chat GPT in learning to write scientific papers. The research data collection technique uses library research in the form of research results and theories that are relevant and in accordance with the purpose of the writing. A literature search was carried out using the Google Scholar and ERIC Document search engines. At the end, this article recommends how to collaborate artificial intelligence with natural writing to produce quality scientific writing. The use of Chat GPT can play a role in the production process of scientific writing while still displaying the creativity and innovation of the writer himself.